Special Issue “Writing Genealogy: Auto/Biographical Research, Autoethnography and Narrative Inquiry”: An Introduction - Helene Connor (Genealogy, 2022)
Writing about genealogy within the ‘academy’ has been hindered by the perception that researching family history and genealogy belongs in the realm of hobbyists as something you might peruse in retirement [...]